Preclinical anti-apoptotic properties of salidroside for hypoxic-ischemic cerebral damage: a systematic review and meta-analysis - Wang Xiaobo; Zhang Yating; Hou Ya; Jiang Hong; Zhang Yi; Zhang Sanyin; Meng Xianli (KeAi Communications Co., Ltd., 2023)
Objective: As the main active ingredient of Tibetan medicine Hongjingtian (Rhodiolae Crenulatae Radix et Rhizoma), salidroside (Sal) has a good anti-apoptotic potential. Currently, there are some conflicting results on the anti-apoptotic mechanisms of Sal. Here we conducted a systematic review and meta-analysis to provide the preclinical evidence of its anti-apoptotic properties in preventing and treating hypoxic-ischemic cerebral damage (HICD). Methods: The literature on the anti-apoptotic potential of Sal in the treatment of HICD from January 1, 1980 to November 9, 2021 was searched online using Chinese databases including Chinese National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang Database, and English databases including PubMed and Web of Science. The quality of the included articles was evaluated by the Cochrane Collaboration network bias risk assessment criteria, and meta-analysis was performed using RevMan 5.3 software. Results: A total of 40 articles were finally included. Among the 40 articles, 30 were about in vivo animal experiments and 17 about in vitro cell experiments, and 7 of them included both animal and cell experiments. After analysis, it was found that Sal had significant effects on disease-related indicators of HICD (P < 0.05), such as cerebral infarctsize and brain water content. As to in vivo studies, Sal mainly affects the expressions of apoptotic factors through anti-inflammation, anti-oxidation, activation of complement pathway, and regulation of signal transduction and autophagy, thus exerting anti-apoptotic potential in treating HICD. While for in vitro studies, Sal plays the anti-apoptotic role in HICD models mainly through anti-oxidation, anti-inflammation, reduction of Ca2+ overload, regulation of mitochondrial function, signal transduction, and C3 complement. Conclusion: Sal can take anti-apoptotic effects to prevent and treat HICD through mechanisms such as anti-inflammation, anti-oxidation, enhanced autophagy, complement and signal transduction, regulation of mitochondrial membrane potential, and reduction of Ca2+ overload.